Ectoparasite Community Structure of Two Bats (Myotis lucifugus and M. septentrionalis) from the Maritimes of Canada - Zenon J. Czenze; Hugh G. Broders (Journal of Parasitology Research)
Prevalence of bat ectoparasites on sympatric Myotis lucifugus and M. septentrionalis was quantitatively characterized in Nova Scotia and New Brunswick by making systematic collections at swarming sites. Six species of ectoparasite were recorded, including Myodopsylla insignis, Spinturnix americanus, Cimex adjunctus, Macronyssu scrosbyi, Androlaelap scasalis, and an unknown species of the genus Acanthophthirius. Male M. lucifugus and M. septentrionalis had similar prevalence of any ectoparasite (22% and 23%, resp.). Female M. lucifugus and M. septentrionalis had 2-3 times higher prevalence than did conspecific males (68% and 44%, resp.). Prevalence of infection of both genders of young of the year was not different from one another and the highest prevalence of any ectoparasite (M. lucifugus 64%, M. septentrionalis 72%) among all bat groups. Ectoparasite prevalence and intensity varied positively with roost group size and negatively with grooming efficacy and energy budgets, suggesting that these variables may be important in ectoparasite community structure.